Three-dimensional high-resolution image inversion and pore level CFD characterisation of effective thermal conductivity of replicated microcellular structures. (May 2022) - Otaru, A.J.; Abdulkadir, M.; Kovo, A.S.; Corfield, M.R.; Tanko, N.; Odey, O.A.; Kenfack, A.; Aroke, U.O.
Abstract: Metallic-based microcellular structures are widely used in heat and mass transfer processes owing to their unique combination of high porosity, high surface area, fixed pore morphology and high Young modulus, enabling their suitability as heat pipes in oil and gas processing equipment, biomedical materials for bone repair and bone substitution, solar collectors, fuel cells, impact loading, soundproofing materials and metallurgical processing. Accurate representation of the effective thermal conductivity of these materials is imperative in understanding their heat transfer mechanisms leading to the design and optimisation of system performance. Due to the limited availability of experimental and predictive data on heat transport phenomena across the interstices of low-porosity microcellular structures - numerically simulated data of effective thermal conductivity for conduction heat transfer in metal foam-fluid systems have been compared for structures typified by near-circular pore walls and openings, i.e. "bottleneck-type" structures and foam porosity ranging between 0.65 and 0.78. A three-dimensional high-resolution image inversion and computational fluid dynamics modelling and simulation of conductive heat transfer for both the fluid and solid domains at pore level is used to estimate effective thermal conductivity for these structures. This approach is extended to structurally-adapted metal foam-fluid systems by broadening the pore volume fraction beyond 0.90 – resulting in the quantification of the fluid phase contribution for heat transfer enhancement and the proposition of empirical constants to support models developed by Calmidi & Mahajan [9] . Findings in this work offer strong support to the supposition that geometrical adaptions of microcellular structures can be used to modulate their effective thermal conductivity and that generalised values of empirical constants may be ambiguous to fully describe conduction heat transfer phenomena in microcellular structures. This approach may prove useful in the design of low-porosity metallic components for applications specific to conduction heat transfer.